LOCAL UNITS EXPRESSING RELIGIOUS BELIEFS - Ganiyeva, Dildora Azizovna; Ibrokhimova, Sarvinoz Ravshanjan kizi (Educational Research in Universal Sciences, 2023)
This article provides information about local units representing religious beliefs.